Analysis and identification of current trends of development of the national market of construction materials ("Journal "U". Economy. Management. Finance.", 2017)
The crisis situation affected many aspects of life of Russians. It did not bypass the construction industry and as a result the related market of construction materials. The research assesses the current state of the construction materials market, presents the results of its analysis and outlines the main trends in its development.
Keywords: construction; construction materials; finishing materials; residential properties